Best practices for ORR performance evaluation of metal-free porous carbon electrocatalysts. (15th April 2022) - Bouleau, L.; Pérez-Rodríguez, S.; Quílez-Bermejo, J.; Izquierdo, M.T.; Xu, F.; Fierro, V.; Celzard, A.
Abstract: Porous carbon materials are promising electrocatalysts for the oxygen reduction reaction (ORR). Their active sites, involving porosity and surface chemistry, are different from those of metal-doped carbons. The latter have been widely studied and are adapted to today's popular electrochemical devices, the rotating disk electrode being the most useful preliminary tool to evaluate their activity in ORR. However, porous carbon materials have been less explored, and experimental parameters need to be adjusted to achieve the best ORR performance. Therefore, in this study, the optimization of different key factors was investigated to evaluate their effect on the ORR performance of porous carbon electrocatalysts in alkaline medium. The parameters considered were: (i) the relevance of using RRDE or Koutecky-Levich equations for estimating the number of electrons transferred; (ii) the amount of ionomer (Nafion®); (iii) the carbon loading on the electrode; (iv) the carbon grinding method; and (v) the selection of the upper potential of ORR experiments. We conclude that an optimization of the experimental conditions should be done for each material studied, and we give important benchmarks for the appropriate evaluation of the catalytic activity in ORR of carbon-based catalysts. Graphical abstract: Image 1